ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA SEKTOR INDUSTRI DI SUMATERA UTARA - Dian Novianti Sitompul (Quantitative Economics Journal, 2014)
North Sumatra is a province that has a fundamental problem of high unemployment. Judging from the years 1994-2010, overall pengengguran is the biggest challenge still facing the North Sumatra due to termination of employment due to the economic crisis, rising raw material prices significantly from the various sub-industries are incorporated in the manufacturing category. On the other hand the costs for labor and increase the added value of the resulting output is a condition that must be considered. This research aims to analyze the influence of GDP, the number of industries, inflation and the minimum wage on employment in the industrial sector of North Sumatra simultaneously and partially.The data used are secondary data sourced from North Sumatra Province namely BPS GDP variable, the number of industries, inflation, wages and employment industries in the province of North Sumatra as time series from 1994 till , 2010. The results of this research can be concluded that simultaneous simultaneously change the variable GDP, inflation, industrial, and UMR significantly affect the demand for industrial labor in the province of North Sumatra. Furthermore, partially concluded that GDP variable, and the number of positive effect on demand for industrial labor industry, while inflation and minimum wage variables negatively affect the demand for industrial labor in the province of North Sumatra.The results also showed that the most dominant variable effect on the demand for labor in the industrial sector of the province of North Sumatra is the number of industries.